(untitled)
On the example of the model reaction of cumene initiation oxidation on kinetic method, the antioxidant properties of ethyl acetate extracts of leaves and fruits of twelve different plants are investigated. Both the content of the antioxidant substances in the studied extracts and their antioxidant activity are defined. It is established that most of the studied extracts of antioxidants contained extracts of Evening Primrose leaves (2.93·10–5 mol/L in 1 mg) and Scarlet amaranth (1.15·10–5 mol/L). The highest antioxidant activity of the extracts from the leaves showed Coneflower (3.21·105 L/mol·s), Pumpkin (2.93·105 L/mol·s), Goosefoot (2.70·105 L/mol·s) and Grecian Silk Vine (2.58·105 L/mol·s). It was shown that oxidation products (Q) of origin antioxidants in the extracts also possess antioxidant activities. Correlation was found between the pre-exponential factor (lgA) and energy activation (E) for the constant rate reaction RO^_2+InH^k_7 ROOH +In^ and RO^_2+Q^k_71 Q^ + ROOH. For constant k7 is established that lgA = 4.9 +0.64 E and for k71 lgA = 2.6 +0.64 E. , number=3 (238), journal=Proceedings of the YSU B: Chemical and Biological Sciences, year=2015, month=Nov., pages=16–22